Pengembangan Media Layanan Berbasis Aplikasi Android Tentang Informasi Studi Lanjut pada Siswa SMP Muhammadiyah 2 Yogyakarta - Cindy Fitriadita; Akhmad Fajar Prasetya (Student Research Journal, 2024)
This study aims to develop an Android application-based service media called INSTULA that provides information related to further study to grade IX students of SMP Muhammadiyah 2 Yogyakarta. Further study information is defined as a collection of data, knowledge, and guidance that helps students understand and choose further education paths according to their potential, interests, talents, and future career prospects. This application contains features such as types of secondary schools (SMA, SMK, MA), interests, simple aptitude tests, and job prospects. The research model used is Research and Development (R&D) with the Borg and Gall approach which is carried out up to the seventh stage, namely product revision. The development process involves validation by material experts, media experts, and service experts. The total results of the expert assessment showed an average score of 90.7 out of 100, with the category "very good." The assessment includes aspects of material, media, and service quality that are declared suitable for use for further study guidance. Based on the results of the Paired Samples t-test conducted to compare the results of the pre-test and post-test, a significant difference was found between the two scores. Descriptively, the average pre-test score was 14.36 with a standard deviation of 2.49, while the average post-test score increased to 18.97 with a standard deviation of 2.02. This average increase indicates a positive effect after the intervention. This increase indicates that the application is effective in supporting students' understanding of further study information. The INSTULA application is declared suitable for use as an innovative media in classical guidance services. This media supports students in exploring further education with an interactive and easily accessible approach, helping them make better educational decisions according to their needs and potential.